Hot corrosion behaviour of Ti–6Al–4V modified by ultrasonic shot peening. (15th November 2016) - Kumar, Sanjeev; Chattopadhyay, K.; Mahobia, G.S.; Singh, Vakil
Abstract: Nanostructure of 17 to 25 nm was developed in surface region of the titanium alloy Ti–6Al–4V, up to the depth of 30 μm, by ultrasonic shot peening. The effect of nanostructured surface was studied on corrosion behaviour of this alloy, in three different salt mixtures: 100 wt.% NaCl, 75 wt.% Na2 SO4 + 25 wt.% NaCl, and 90 wt.% Na2 SO4 + 5 wt.% NaCl + 5 wt.% V2 O5 ; at 400, 500 and 600 °C. Specimens were subjected to heating and cooling cycles with different hold periods in three blocks for total exposure of 100 h. The main corrosion products formed in the different salt mixtures were characterized as TiO2, Al2 O3, V2 O3, Ti2 O3 and V2 O5 oxides. The corrosion rate was found to be lower in the ultrasonic shot peened specimens as compared to those in the non-shot peened ones. Graphical abstract: Highlights: Surface nanostructure was produced by ultrasonic shot peening on alloy Ti–6Al–4V. Hot corrosion resistance was enhanced due to surface nanostructuring. 100% NaCl salt was most detrimental corrosion resistance. Corrosion resistance of shot peened sample increased due to double oxide layer.